Dissolution susceptibility of glass-like carbon versus crystalline graphite in high-pressure aqueous fluids and implications for the behavior of organic matter in subduction zones. (15th March 2020) - Tumiati, Simone; Tiraboschi, Carla; Miozzi, Francesca; Vitale-Brovarone, Alberto; Manning, Craig E.; Sverjensky, Dimitri A.; Milani, Sula; Poli, Stefano
Abstract: Organic matter, showing variable degrees of crystallinity and thus of graphitization, is an important source of carbon in subducted sediments, as demonstrated by the isotopic signatures of deep and ultra-deep diamonds and volcanic emissions in arc settings. In this experimental study, we investigated the dissolution of sp 2 hybridized carbon in aqueous fluids at 1 and 3GPa, and 800 °C, taking as end-members (i) crystalline synthetic graphite and (ii) X-ray amorphous glass-like carbon. We chose glass-like carbon as an analogue of natural "disordered" graphitic carbon derived from organic matter, because unlike other forms of poorly ordered carbon, it does not undergo any structural modification at the investigated experimental conditions, allowing approach to thermodynamic equilibrium. Textural observations, Raman spectroscopy, synchrotron X-ray diffraction and dissolution susceptibility of char produced by thermal decomposition of glucose (representative of non-transformed organic matter) at the same experimental conditions support this assumption. The redox state of the experiments was buffered at ΔFMQ ≈ –0.5 using double capsules and either fayalite-magnetite-quartz (FMQ) or nickel-nickel oxide (NNO) buffers. At the investigated P–T–f O2 conditions, the dominant aqueous dissolution product is carbon dioxide, formed by oxidation of solid carbon. At 1GPa and 800 °C, oxidative dissolution of glass-like carbon produces 16–19 mol% more carbon dioxide than crystalline graphite. In contrast, fluids interacting with glass-like carbon at the higher pressure of 3GPa show only a limited increase in CO2 ( f H2 NNO ) or even a lower CO2 content ( f H2 FMQ ) with respect to fluids interacting with crystalline graphite. The measured fluid compositions allowed retrieval of the difference in Gibbs free energy (Δ G ) between glass-like carbon and graphite, which is +1.7(1) kJ/mol at 1GPa–800 °C and +0.51(1) kJ/mol ( f H2 NNO ) at 3GPa–800 °C. Thermodynamic modeling suggests that the decline in dissolution susceptibility at high pressure is related to the higher compressibility of glass-like carbon with respect to crystalline graphite, resulting in G – P curves crossing at about 3.4GPa at 800 °C, close to the graphite–diamond transition. The new experimental data suggest that, in the presence of aqueous fluids that flush subducted sediments, the removal of poorly crystalline "disordered" graphitic carbon is more efficient than that of crystalline graphite. This occurs especially at shallow levels of subduction zones, where the difference in free energy is higher and the availability of poorly organized metastable carbonaceous matter and of aqueous fluids produced by devolatilization of the downgoing slab is maximized. At depths greater than 110 km, the small differences in Δ G imply that there is minimal energetic drive for transforming "disordered" graphitic carbon to ordered graphite; "disordered" graphitic carbon could even be energetically slightly favored in a narrow P interval.